Dietary fibre manipulation as a potential endogenous mechanism of radiosensitisation in bladder cancer - Then, CK (2022)
New non-toxic radiosensitisers are needed in the treatment of muscle-invasive bladder cancer because elderly patients are very vulnerable to chemotherapy-related toxicity of currently available radiosensitisers. Our previous study showed that high fibre diets sensitised RT112 xenografts to irradiation by modifying the gut microbiota and this phenotype was positively correlated with Bacteroides acidifaciens (BA) abundance. As the gut microbiota can enhance anti-tumoural immune responses, I hypothesised that dietary fibre manipulation and its effects on the gut microbiota can radiosensitise tumours via microbiota secretion of metabolites and/or immunomodulation.